Resource Allocation for Massive Multiple Input Multiple Output Based Communications Systems - Özbek, Berna; Yılmaz, Saadet Simay; Yılmaz, Saadet Simay; Özbek, Berna; Yılmaz, Saadet Simay (01. Izmir Institute of Technology, 2023)
In this thesis, we examine resource allocation strategies for massive multiple-input and multiple-output (MIMO) based wireless communications systems to increase system performance, considering computation-intensive applications with low-latency communication. Firstly, we propose user selection algorithms for non-orthogonal multiple-access (NOMA)-based massive MIMO systems in densely deployed scenarios to increase the sum data rate. Then, we investigate mobile edge computing (MEC) as a solution to enable computation-intensive and delay-critical applications. We propose resource allocation algorithms considering the downlink and uplink transmit powers, the task offloading decision factor and the computing resources to reduce both transmission and computing delays for the massive MIMO-NOMA-assisted MEC system. Finally, we consider a cooperative MEC system where helpers assist in the execution of cell-edge users' computation-intensive tasks with low latency. On the other hand, the task offloading in MEC can introduce security concerns as the offloaded data may be intercepted and overheard by eavesdroppers. Since ensuring a secure task offloading scheme in MEC is important, we formulate the optimization problem to minimize both offloading and computing delays while satisfying security constraints for a massive MIMO-based cooperative MEC. We provide performance results based on sum data rate, delay and total offloading data for the proposed schemes in massive MIMO based wireless communication systems.

Bu tezde, düşük gecikmeli haberleşme ile yoğun hesaplama gerektiren uygulamalar için, sistem performansını artırmak amacıyla yoğun çok girişli ve çok çıkışlı (MIMO) kablosuz iletişim sistemlerinde kaynak tahsisi stratejileri incelenmektedir. Öncelikle, toplam veri hızını artırmak amacıyla yoğun olarak konuşlandırılmış senaryolarda dikgen olmayan çoklu erişim (NOMA) tabanlı yoğun MIMO sistemleri için kullanıcı seçim algoritmaları önerilmektedir. Ardından, yoğun hesaplama gerektiren ve gecikme açısından kritik olan uygulamaları gerçekleştirmek için bir çözüm olarak mobil uç hesaplama (MEC) sistemi incelenmektedir. Yoğun MIMO-NOMA destekli MEC sistemi için, hem iletim hem de hesaplama gecikmelerini azaltmak amacıyla aşağı bağlantı ve yukarı bağlantı iletim güçlerini, görev iletim karar faktörünü ve hesaplama kaynaklarını dikkate alan kaynak tahsis algoritmaları önerilmektedir. Son olarak, yardımcıların düşük gecikme süresiyle hücre ucundaki kullanıcıların yoğun hesaplama gerektiren görevlerini yürütmesine yardımcı olan işbirlikçi bir MEC sistemi dikkate alınmaktadır. Öte yandan, MEC'de görev iletimi sırasında, verilerin gizli dinleyiciler tarafından engellenebilir ya da duyulabilir olması güvenlik sorunu yaratabilir. MEC'de güvenli bir şekilde görev iletimini sağlamak önemli olduğundan, yoğun MIMO tabanlı işbirlikçi MEC sisteminde güvenlik kısıtlamaları göz önünde bulundurularak, hem iletim hem de hesaplama gecikmelerini en aza indirmek için bir optimizasyon problemi formüle edilmektedir. Yoğun MIMO tabanlı kablosuz ileti¸sim sistemlerinde, önerilen şemalar için toplam veri hızı, gecikme ve toplam iletilen veriye dayalı performans sonuçları sağlanmaktadır.
Yoğun Çok Girişli Çok Çıkışlı Haberleşme Sistemleri için Kaynak Tahsisi
Thesis (Doctoral)--İzmir Institute of Technology, Electrical and Electronics Engineering, Izmir, 2023
Includes bibliographical references (leaves. 115-129)
Text in English; Abstract: Turkish and English
Keywords: Massive MIMO; MIMO systems; NOMA; Communication systems